Sponsoring the Arts: Melic Perspectives - Athanassaki, Lucia (Classica - Revista Brasileira de Estudos Clássicos, 2018)
This paper explores the melic poets’ take on art and its sponsors. Since much has been written on the relationship of epinician poets with their patrons, this paper broadens the focus of enquiry to include other melic genres and, in addition to the verbal, to look at the visual arts as well, i.e. melic representations of communities that sponsor songs and of communities or individuals that sponsor other art-forms such as sculpture, architecture, and precious objects. Taking as starting point Xenophon’s depiction of Simonides in Hiero, I discuss epigrams XXVII and XXVIII Page and relevant testimonia that show Simonides’ keen interest in Athenian dithyrambic contests; Bacchylides’ Ode 19, probably composed for the Great Dionysia; Pindar’s Pythian 7, Paean 8, and fragment 3 in conjunction with Homeric Hymn to Apollo 281-99, Herodotus 1.31, Cicero, De oratore 2. 86. 352-353, [Plutarch] Consolatio ad Apollonium, and Pausanias – all of which offer precious insights into Pindar’s views on sponsoring monumental sculpture and architecture; and Bacchylides’ description of the golden tripods that Hieron offered to Apollo in Ode 3. On the basis of this evidence I argue that whatever the nature and the range of remuneration of poets and artists may have been, melic rhetoric shows that it was the relationship of poets, artists and their sponsors with the gods that was ultimately at stake. This is why both the poetry and the traditions about Simonides, Pindar and Bacchylides privilege the divine favour that poets, artists and patrons alike either obtained or were hoping to obtain by offering masterpieces to the gods.